PENGARUH NET PROFIT MARGIN, RETURN ON EQUITY, RETURN ON ASSET TERHADAP HARGA SAHAM PERUSAHAAN PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2020 - Roichatul Jannah; Moh. Azus Shony Azar; Fatichatur Rachmaniyah (J-MACC, 2021)
This study aims to determine the effect of Net Profit Margin, Return On Equity, and Return On Assets, on the Share Prices of Coal Mining Companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The data used in this study is secondary data that has been documented by the IDX. The analysis technique used is multiple linear regression. The results of the research on the t-test showed that the Net Profit Margin partially positive effect on the stock price. However, Return On Equity, and Return On Assets have no effect on stock prices. The F test shows that Net Profit Margin, Return On Equity, and Return On Assets have an effect on the stock price of coal mining companies listed on the Indonesia Stock Exchange for the 2015-2020 period.